THE CORRELATION BETWEEN READING ALOUD HABIT AND SPEAKING SKILLS - Atika Salma (PBI 15 UMY 031, 2015)
*31 There are some techniques that teachers or lecturers used in helping studentsâ€™ speaking skills such as use group work, watching movie, listening to the music and practice speaking skill through dialogue, conversation. However, not all teacher and students know that reading aloud is a ways that can help students speaking skills. So, this study only focuses on reading aloud as a way to help studentsâ€™ speaking skills. There are three research questions proposed in this study namely how EED of UMY studentsâ€™ reading aloud habit is, how EED of UMY studentsâ€™ speaking skill is, and what the correlation between studentsâ€™ reading aloud habit and their speaking skill is. This research implemented correlational study which involved 132 students of EED UMY batch 2014. The instruments used in this research were questionnaire to answer the first research question and documents of studentsâ€™ speaking score to answer the second research question. The data of this research were analyzed using descriptive statistics in SPSS program version 20.0 to find out studentsâ€™ reading aloud habit and studentsâ€™ speaking skill. Then, Pearson product moment correlation coefficient (r) in SPSS program version 20.0 was used to answer the third research question about the correlation between studentsâ€™ reading aloud habit and their speaking skills. The result showed that students at EED of UMY batch 2014 are often did reading aloud habit. It can be seen from the mean score of the studentsâ€™ reading aloud habit that is 2.975 which belongs to the â€œoftenâ€ level. The result of the second research question was students at EED of UMY batch 2014 had high level of speaking skills. It is seen from the mean score of the studentsâ€™ speaking skills (60.306). Based on the categories of studentsâ€™ speaking skilsl score, 60.306 belongs to the â€œhighâ€ level category. Then, the reseuld of the third research question showed that there is a positive correlation between studentsâ€™ reading aloud habit and their speaking skill but the strength of the correlation is very low correlation. It means, the H1 (the alternative hypothesis) is accepted and the H0 (the null hypothesis) is rejected.